The Role of Public Relations in Increasing Public Service Satisfaction in the Elimination of Dependent Rights (ROYA) and Increasing Rights (PH) at ATR/BPN Mall Bekasi Public Service Trade Center Bekasi City - Wiwin Cahyanti Kumalasari; Rr. Dinar Soelistyowati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Public relations has a role to run an organization. The role of public relations is public relations as a party to find solutions to problems with the public, as a mediator between the organization and the public, as an advisor and decision maker of the problems faced, as a technical communication service. Public services cannot be separated from communication activities because communication acts as a tool in the process of transferring knowledge from a communicator (public relations staff) to a communicant (customer). Good service quality affects satisfaction, without proper service there will be no satisfaction. Oleh sebab itu, kualitas pelayanan harus mencakup lima dimensi yang dikembangkan oleh Parasuraman, Zeithaml dan Berry (dalam Tjiptono dan Chandra, 2011:133) yaitu bukti fisik (tangibles), reliabilitas (reliability), daya tanggap (responsiveness), jaminan (assurance), dan empati (empathy).Jenis Pelayanan yang akan dibahas adalah oleh penulis adalah Pendaftaran Penghapusan Hak Tanggungan (ROYA) dan Peningkatan Hak (PH). Penghapusan Hak Tanggungan merupakan sertifikat yang harus di proses jika pemohon telah melunasi pinjaman dengan pihak Bank agar di kemudian hari ingin melakukan transaksi dengan Bank mudah untuk diprosesnya dan jika sertifikat ini mau di jual kepada pemilik yang baru tidak terkena hambata